POTENTIAL DEVELOPMENT FOR COMPETITIVENESS ENHANCEMENT OF COMMUNITY ENTERPRISES IN THAILAND’S SOUTHERN BORDER PROVINCES - Sangayotin, Taksaya (RMUTT Global Business and Economics Review, 2022)
The objective of this research were to analyze the problems of community enterprises and propose the guidelines for the potential development for competitiveness enhancement of community enterprises in Thailand. This was the qualitative research method using the in-depth interview with the entrepreneurs of community enterprises and the Outside-in. The study is in the southern borderal provinces of Thailand. The research results revealed that the operations of Community Enterprises in Thailand’s Southern Border Provinces showed the problems of labor shortage in manufacturing process and manufacturing technology, the lack of digital marketing knowledge and product development, and also the lack of channel of distribution. In term of finance and accounting, it did not have the appropriate base costing system, and accessing the proper funding sources, the lack of management knowledge, and attitude adjustment of members for accepting the change, lack of participation of networks and problem solving by increasing competition advantage. In term of production, it should give knowledge and necessary skills for development, promoting the leadership to members. In term of demand, it should produce goods towards the customer needs, building brand salience. In term of related industries, cooperating with building of business ecosystems. In term of strategies, organization, and competition, it should make the highlight to the online marketing and build the innovative communication throughout the platform, storytelling through the identity and the local wisdom, building creative economy within the community, and the government sector should support all useful areas and also develop any possible advantages. Moreover, the Outside-In approach was used to build the professionalism and sustainability within the community enterprises.